2015
DOI: 10.1155/2015/972067
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Andrographolide as a Potent Inhibitor of NS3-4A Protease and Its Drug-Resistant Mutants UsingIn SilicoApproaches

Abstract: Current combination therapy of PEG-INF and ribavirin against the Hepatitis C Virus (HCV) genotype-1 infections is ineffective in maintaining sustained viral response in 50% of the infection cases. New compounds in the form of protease inhibitors can complement the combination therapy. Asunaprevir is new to the drug regiment as the NS3-4A protease inhibitor, but it is susceptible to two mutations, namely, R155K and D168A in the protein. Thus, in our study, we sought to evaluate Andrographolide, a labdane-diterp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Hepatitis C virus (HCV) is a widely studied viral model, and using CADD methods a natural bicycle diterpene was evaluated by molecular docking. This diterpene interacts with both, the native and the mutated structures of the HCV NS3-4A protease, with a docking score of -15.1 kcal/mol, and this interaction was mediated mainly by the presence of hydrogen bonds between the ligand and S, A and H amino acids in the target protein [5]; in our study, the best interaction between subti1 and HEV capsid protein showed a docking score of -7.0 kcal/mol and was also mediated by the presence of A504 in chain A of the HEV capsid protein, forming two hydrogen bonds ( Table 2). In a similar way, bioflavonoids showed a promissory anti-HCV helicase activity, with high docking scores and with residues D and S as the main amino acids participating in the interaction [13]; these residues were also mediating the interaction of HEV capsid protein and the AVPs designed in our study, suggesting that D and S could be crucial for AVPs interactions ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis C virus (HCV) is a widely studied viral model, and using CADD methods a natural bicycle diterpene was evaluated by molecular docking. This diterpene interacts with both, the native and the mutated structures of the HCV NS3-4A protease, with a docking score of -15.1 kcal/mol, and this interaction was mediated mainly by the presence of hydrogen bonds between the ligand and S, A and H amino acids in the target protein [5]; in our study, the best interaction between subti1 and HEV capsid protein showed a docking score of -7.0 kcal/mol and was also mediated by the presence of A504 in chain A of the HEV capsid protein, forming two hydrogen bonds ( Table 2). In a similar way, bioflavonoids showed a promissory anti-HCV helicase activity, with high docking scores and with residues D and S as the main amino acids participating in the interaction [13]; these residues were also mediating the interaction of HEV capsid protein and the AVPs designed in our study, suggesting that D and S could be crucial for AVPs interactions ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several clinical trials demonstrate its positive effects on infectious disease, autoimmune disorders and it has a potential effect against viral defenses [44,50,52]. Moreover, it exerts anti-viral activity towards a number of different viruses including HIV, hepatitis B, herpes simplex, influenza, hepatitis C, chikungunya virus (CHIKV), Epstein-Barr virus (EBV), human papillomavirus (HPV) dengue virus (DENV) and others [51,56,57,[61][62][63][64][65][66][67][68][69][70][71][72]. Recent studies showed that andrographolide is a potential inhibitor of the main protease of SARS-CoV-2 through in silico studies, such as molecular docking, target analysis, toxicity prediction and ADME prediction (absorption, distribution, metabolism, and excretion) [57].…”
Section: Impact Of Andrographolide and Viral Infectionsmentioning
confidence: 99%
“…Moreover, andrographolide was reported to inhibit HCV protein synthesis, RNA replication and infection[101]. Detailed mechanisms showed that andrographolide activates p38 MAPK phosphorylation and stimulates Nrf2-mediated heme oxygenase (HO)-1 expression, thereby increasing the amounts of its metabolite biliverdin, which was found to activate the antiviral IFN response and suppress HCV NS3/4A protease activity[101,102]. These findings support a clinical trial of andrographolide and its derivatives for the treatment of severe CHC.…”
Section: Anti-inflammatory/hepatoprotective Therapy In Hcv Infectionmentioning
confidence: 99%